Close-up view of an ongoing merger between the NGC 4839 group and the Coma cluster. Issue Volume 14:Issue S342(2018) (May 2018) - Lyskova, Natalia; Churazov, Eugene; Zhang, Congyao; Forman, William; Jones, Christine
Abstract: We analyse archival XMM-Newton observations of the massive galaxy group NGC 4839 falling into the Coma cluster core, which reveal a complex morphology for the merger. By comparing high quality X-ray maps of the merging subcluster with SPH simulations, we propose an infall scenario which qualitatively reproduces the observed structure of the NGC 4839 tail.